Research citations building trust in Wikipedia: Results from a survey of published authors - Carlos Areia; Kath Burton; Mike Taylor; Charles Watkinson (PLoS ONE, 2025)
The use of Wikipedia citations in scholarly research has been the topic of much inquiry over the past decade, however little is known regarding perceived Researchers trustworthiness of Wikipedia citations and representation of their work. This cross-publisher study (Taylor & Francis and University of Michigan Press) aimed to investigate author sentiment towards Wikipedia as a source of trusted information. Methods A short survey was distributed to 40,402 authors of papers cited in Wikipedia (n=21,854 surveys sent, n=750 complete responses received). The survey gathered responses from published authors in relation to their views on Wikipedia’s trustworthiness in relation to the citations to their published works. The unique findings of the survey were analysed using a mix of quantitative and qualitative methods using Python, Google BigQuery and Looker Studio. Results Overall, authors expressed positive sentiment towards research citation in Wikipedia and researcher engagement practices (mean scores >7/10). Sub-analyses revealed significant differences in sentiment based on publication type (articles vs. books) and discipline (Humanities and Social Sciences vs. Science, Technology, and Medicine), but not access status (open vs. closed access). Conclusions This study provides unique insights into author perceptions of Wikipedia’s trustworthiness. Further research is needed to deepen the understanding of the benefits for researchers and publishers including academic citations in Wikipedia.